Kuala Lumpur International Book Fest: UMP Publisher among the 10 best university publishers - Muhammad Azli, Shukri (Penerbit UMP, 2013)
UMP Publisher made a new record sale at the Kuala Lumpur International Book Fest 2013 that was held from April 26 until May 4 at PWTC.